4CPS-011 Prescription analysis of direct acting oral anticoagulants. (24th March 2020) - Soto, I; Rubio, B; Mañes, M; Solis, J; Bertran De Lis, B; Gómez, EP; Maroto, E; Bernias, MI; Sollano, I; Morona, I; Moriel, C
Abstract : Background and importance: The use of direct acting oral anticoagulants (DOACs) has increased in recent years. Their posology and adverse effects require pharmaceutical monitoring in order to guarantee effective and safe treatment. Aim and objectives: To analyse the prescription and utilisation criteria for DOACs in clinical practice as well as the acceptance of the pharmaceutical recommendations made. Material and methods: This was a longitudinal prospective descriptive study of patients treated with DOACs (apixaban, rivaroxaban and dabigatran) admitted to a second level hospital (September 2018–March 2019). The information sources used were: Farmatools, Selene, Prescription Single Module and Horus. The variables analysed were: demographics, drugs prescribed, prescriptor service, indications, previous treatments, cause of the change, funding and pharmaceutical interventions. Results: Seventy-three patients were analysed (50.68% women; median age 82 years (IQR 73–87): 50.68% were treated with apixaban, 30.14% with dabigatran and 19.18% with rivaroxaban. The main prescriber services were: cardiology (49.32%), internal medicine (30.13%) and geriatrics (9.59%). Reasons for treatment were: 97.26% for atrial fibrillation, 1.37% for deep vein thrombosis and 1.37% for pulmonary thromboembolism. A total of 80.82% had previously received treatment with acenocoumarol, 5.48% with DOACs and 13.70% had not received previous treatment. The main reasons for the change from acenocoumarol to DOACs were: poor control of the international normalised ratio (INR) (59.32%), vascular accident (15.26%) and haemorrhagic event (10.7%). Modifications from rivaroxaban to apixaban were observed in three patients: chronic kidney failure, age adjustment with kidney failure and haematological data altered. In addition, we observed a change from dabigatran to apixaban for gastritis. A total of 90.41% of patients had their treatment funded by the national health system. Dose adjustment was needed in 52.05% of patients, of which 86.84% were correctly made by the physician and 13.16% required pharmaceutical intervention due to kidney failure, age and/or weight, with a 60% acceptance rate. Conclusion and relevance: The most used DOAC was apixaban, prescribed mainly by cardiologists to patients with atrial fibrillation, as opposed to acenocoumarol, mainly prescribed by haematologists. Most patients had previously been treated with acenocoumarol, failing on this treatment due to poor INR control. Most had their treatment funded by meeting the funding criteria. Dose adjustments were carried out, receiving a highly acceptance rate. References and/or acknowledgements: No conflict of interest.